Sensitive skin: an update on the aesthetic medicine management through a mini review and a focus on dermocosmetics - Fulgione, Elisabetta; Secchi, Maura; Di Paolo, Josephine; Veraldi, Maria; Alessandrini, Giuseppe; Bianchi , Elisabetta; Robuffo, Silvia; Bartoletti, Emanuele (Aesthetic Medicine, 2025)
Background: Sensitive skin is a condition characterized by an exaggerated response to environmental, chemical, and physiological stimuli, often manifesting as discomfort, itching, burning, and redness.  It is a global and common condition with a reported prevalence of 50-70% in the adult population, with symptoms varying widely in severity and triggers. Furthermore, sensitive skin is often associated with conditions like rosacea and atopic dermatitis. The underlying etiopathogenetic mechanism of sensitive skin is multifactorial, involving a compromised skin barrier, heightened nervous system outputs, and dysregulated immune system responses.Aim: To summarize current literature on sensitive skin, elucidate its underlying mechanisms, and provide guidance for management strategies to support affected individuals in daily life.Methods: A mini review of recent literature was conducted, focusing on the pathophysiology, prevalence, associated conditions, and management approaches for sensitive skin.Results: The high prevalence of the condition has led to summarize in this mini- review current literature and to comment the latest data available to support subjects with sensitive skin in their everyday life. Management of sensitive skin involves a combination of avoidance of known triggers, use of gentle skincare products formulated to minimize irritation, and maintenance of a healthy skin barrier. Components such as ceramides, hyaluronic acid, and niacinamide are commonly recommended for their soothing and barrier-repairing properties.Conclusions: Effective management of sensitive skin requires a tailored treatment focused on protection, hydration, and the least possible product use to reduce the risk of exacerbations and maintain skin health.